(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study deals with the subject of the main trends of Turkish and American foreign policy towards a strategic region, which is the Middle East, especially after 2011, which was characterized by the severity of competitions and complex geopolitical crises in that region, such as the crises of countries (Libya, Yemen, Tunisia, Syria), and the study focused on analyzing the changes In the basic directions of the policy of each of the two countries during the years 2011-2022, and their effects and potential results, and as the study touched on in detail the most important orientations of the three American administrations (Obama, Trump, Biden) and the strategies of those administrations about setting general lines towards the Middle East, and as for the directions The study focused on the most important plans, programs and strategies of the Justice and Development Party led by Erdogan. The study also addressed the most important points of convergence and divergence between the basic trends of American and Turkish policies toward the Middle East. The study reached a set of results, the most important of which are related to the nature of the impact of regional and international variables on The Middle East region, as well as the impact of the repercussions of the Russian-Ukrainian war, and the impact of changing US administrations Three (Obama, Trump, Biden) on the orientations of Turkish and American foreign policy towards the Middle East.